Epichloë endophytes improved Leymus chinensis tolerance to both neutral and alkali salt stresses - Yin, Lijia; Wei, Maoying; Wu, Guanghong; Ren, Anzhi (Frontiers in Plant Science, 2022)
Symbiotic relationships with microbes may influence how plants respond to environmental change. In the present study, we tested the hypothesis that symbiosis with the endophytes promoted salt tolerance of the native grass. In the field pot experiment we compared the performance of endophyte-infected (E+) and endophyte-uninfected (E−) Leymus chinensis, a dominant species native to the Inner Mongolia steppe, under altered neutral and alkaline salt stresses. The results showed that under both neutral and alkaline salt stresses, endophyte infection significantly increased plant height, leaf length and fibrous root biomass. Under neutral salt stress, endophyte infection decreased Na+ content and Na+/K+ ratio (p=0.066) in the leaf sheath while increased Ca2+ and Mg2+ content in the rhizome. Under alkali salt stress, endophyte infection tended to increase K+ content in the fibrous root, enhance Mg2+ content in the fibrous root while reduce Na+/K+ ratio in the leaf blade in the 100 mmol/L alkali salt treatment. Although endophyte-infected L. chinensis cannot accumulate Na+ high enough to be halophytes, the observed growth promotion and stress tolerance give endophyte/plant associations the potential to be a model for endophyte-assisted phytoremediation of saline-alkaline soils.